The crusades : [videorecording (DVD)] : crescent & the cross - Lewis, Mark (A&E Home Video ; Distributed by New Video, 2005)
Using CGI-enhanced visuals and dramatic reenactments, The History Channel brings the key battles of the Crusades to life. See rare locations, including a vast chain of Crusader castles and get a feel of what day-to-day life was like.